KONSELING RESOLUSI KONFLIK UNTUK MENINGKATKAN PERSEPSI POSITIF TERHADAP KONFLIK DAN SIKAP KOLABORATIF PADA SISWA - Budi Purwoko (Elementary: Islamic Teacher Journal, 2016)
This research examined the effectiveness of conflict resolution counseling to solve student’s interpersonal conflict in senior high school. The experimental study used randomized controlled trials design with triple blinding include: clien as participants, counselors, and pretest-postest administrator. Participants were 24 students with destructive interpersonal, devided into 12 students in the experimental group and 12 students in the control group. Participants in the experimental group received conflict resolution counseling and participants in the control group received counseling as usual. Based on anacova statistical test indicated implementing of conflict resolution counseling has improved: (1) positive perceptions of the conflict, (2) collaborative attitude in the face of conflict. It can be concluded that, conflict resolution counseling can help the students of senior high school to solve their interpersonal conflicts. Conflict resolution counseling can be adopted as alternative counseling for interpersonal conflict resolving.